METHANE EFFLUX IN RICE PADDY FIELD UNDER DIFFERENT IRRIGATION MANAGEMENTS - Diovane Freire Moterle (Revista Brasileira de Ciência do Solo, 2013)
Paddy rice fields may contribute to methane (CH4) emission from soil due to anaerobic conditions after flooding. Alternatives to continuous flooding irrigation in rice have been developed to mitigate CH4 efflux into the atmosphere. This study aims to investigate the effects of irrigation managements in the CH4 efflux during the rice growing season. An experiment was carried out at in Santa Maria, Rio Grande do Sul State, Brazil, during 2007/08 and 2009/10 growing seasons. The treatments were continuous flooding and intermittent irrigation in 2007/08 and continuous flooding, intermittent irrigation and flush irrigation in 2009/10. Intermittent irrigation is effective in mitigating CH4 efflux from rice fields when climatic conditions enable water absence during cultivation, but its efficiency depends on the electrochemical soil conditions during the flooding cycles.